Economic Operation of Hybrid Power Plant The Wind In Bantul D.I. Yogyakarta - Winardi, Bambang; Imam Santoso; Aris Triwiyatno (PT. Banjarese Pacific Indonesia, 2024)
Hybrid Power Plants (PLTH) are power plants consisting of PLTS with wind turbines. The Bayu Baru PLTH must be regularly evaluated because the PLTH components are susceptible to damage. This evaluation aims to ensure that electrical energy continuity is maintained. PLTH performance can be measured through the performance of each generation component. The performance of PLTH solar panels and wind turbines can be measured from the output power of these components. With HOMER software simulation, you can calculate the economic level of a hybrid generating system based on the lowest NPC value. Simulation results with HOMER software show that the most economical generating components in PLTH are wind turbines with a capacity of 5kW and 2.5kW based on LCOE values ​​of 0.190 and 0.171/kWh.